Nutritional and phytochemical properties of Opuntia ficus-indica (L.) Miller fruits from Portugal - Gomes, A. (2019)
Opuntia ficus-indica, commonly referred to a cactus pear, belongs to the Cactaceae family, characyerized by a remarkable adaptation to arid and semi-arid climates, in tropical and subtropical regions of the globe. In Portugal, it is known as "figueira do diabo". The fruit can be used in the production of jams, in cosmetic applications and folk medicine, based on its bioactive compounds and biological/pharmacological properties.